Educação profissional e filantropia capitalista: dimensões e significados de um projeto de Responsabilidade social empresarial - Diniz, Paulo Vinicius Lamana (2010)
From a theoretical fundamentally grounded in Marxist (and Marxian) theory, the following paper seeks to analyse and reveal the objectives of a project of professional education for poor teenagers, in the aspects of so-called corporate social responsibility . For this, and directly related to the project, was important to describe the characteristics and measures of developed capitalist philanthropy in contemporary Brazil, as well as, to contribute to this, the deep changes in the pattern of state intervention (political society) capitalist. The philanthropy project, research object of present paper, was an important tool of business hegemony.